Pembangunan Perpustakaan sebagai Pendukung Literasi Pemuda di Desa Tambelang, Kecamatan Krucil, Kabupaten Probolinggo - Septiandika, Verto; Maksin, Mastina; Yudianto, Eko Yunus; Puspitarini, Renny Candradewi; Sucahyo, Imam; Mubaroq, Alvan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The Library Development Program as a Support for Youth Literacy in Tambelang Village, Krucil District, Probolinggo Regency aims to enhance literacy among youth in Tambelang Village by providing adequate village library facilities. The implementation method includes location surveys, development planning, procurement of books and other supporting facilities, and community outreach. The program's results show an increase in reading interest and literacy activities among village youth. The library built has become a center for learning and self-development for the people of Tambelang Village, particularly the younger generation. This program is expected to be sustainable and have a long-term impact on improving the quality of human resources in Tambelang Village, Krucil District, Probolinggo Regency.